A dual-function molecularly imprinted optopolymer based on quantum dots-grafted covalent-organic frameworks for the sensitive detection of tyramine in fermented meat products. (30th March 2019) - Zhang, Dianwei; Liu, Huilin; Geng, Weitao; Wang, Yanping
Graphical abstract: Highlights: A dual-function MIOP based on QDs-grafted COFs was developed. It was used to detect tyramine by optosensing and SPE–HPLC simultaneously. MIOP were low-cost and commercial- availability to encourage large-scale application. Optosensing based on MIOP exhibited a rapid and selective detection. SPE–HPLC based on MIOP had a good accuracy, sensitivity, and selectivity. Abstract: Molecular imprinting is a technique for polymerization using a template molecule to produce cavities in the polymer with high selectivity. The successful synthesis of a dual-function molecularly-imprinted optopolymer (MIOP) based on quantum dots-grafted covalent-organic frameworks as adsorbents has allowed the simultaneous detection of tyramine by optosensing and solid-phase extraction coupled with high performance liquid chromatography (SPE–HPLC). The MIOP, obtained by a one-pot reverse microemulsion polymerization, selectively measured tyramine from fermented meat products. Under optimized conditions, the relative fluorescence intensity of the optosensing method increased linearly at tyramine concentrations from 35 to 35, 000 µg/kg, with a detection limit of 7.0 µg/kg. For SPE–HPLC, the linear range was from 20 to 2000 µg/kg, with a detection limit of 5 µg/kg. The optosensing based on MIOP is a rapid and selective method that would be suitable for detecting TYM in food, while SPE–HPLC also provided good levels of accuracy, sensitivity, and selectivity.